Pigmented paraganglioma of the kidney: a case report - Zhao Ling; Luo Jie; Zhang Honglei; Da Jiping (BMC, 2012)
Abstract Paragangliomas are rare neoplasms arising from undifferentiated cells of the primitive neural crest. We report a case of a 57-year-old patient with renal pigmented paraganglioma that was an incidental finding. Histopathological examination showed typical morphology of paraganglioma, as well as the unusual feature of large amounts of pigment in the cytoplasm of the tumor cells which was confirmed by bleached Fontana-Masson. Electron microscopy showed abundant, pleomorphic electron-dense granules consistent with neuromelanin. The tumor cells were positive for CD56 and chromogranin A, negative for HMB-45. The unique morphologic appearance represents divergent differentiation from neural crest. To our knowledge, the present case represents the first example of pigmented paraganglioma of the kidney. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2017147293711495.